2008
DOI: 10.1007/s10900-008-9093-9
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Centers and Emergency Preparedness: An Assessment of Competencies and Training Needs

Abstract: Community health centers (CHCs) provide care to a large number of medically underserved Americans. As primary care providers and trusted members of their communities, CHCs need to be prepared to respond to emergency and disaster situations, as they may be relied upon for medical care and other support services. Focus groups were conducted with CHC medical directors and administrators from New York City. Participants discussed previous emergency preparedness training, future training needs, applicability of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
0
28
0
4
Order By: Relevance
“…Emergency preparedness competencies have been referenced in the literature and are considered critical for educating and preparing a health care work force to respond competently to a disaster event. Ablah, Tinius, Horn, Williams, and Gebbie (2008) espoused that having a standardized list of emergency response competencies will assist in the development and evaluation of education and training programs. The authors acknowledged that while emergency preparedness competencies have been developed for specific health professionals, including nurses and public health workers, institutionally oriented community health centers have been overlooked.…”
Section: Emergency Preparedness Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency preparedness competencies have been referenced in the literature and are considered critical for educating and preparing a health care work force to respond competently to a disaster event. Ablah, Tinius, Horn, Williams, and Gebbie (2008) espoused that having a standardized list of emergency response competencies will assist in the development and evaluation of education and training programs. The authors acknowledged that while emergency preparedness competencies have been developed for specific health professionals, including nurses and public health workers, institutionally oriented community health centers have been overlooked.…”
Section: Emergency Preparedness Competenciesmentioning
confidence: 99%
“…The authors concluded that the effectiveness of training is dependent on factors such as assessing the needs of the target audience, the methodology in which training is delivered, and the number of training opportunities offered. Ablah et al (2008) used a focus group approach to explore the learning needs of community health center (CHC) clinicians from New York by assessing CHC directors' and administrators' perceptions of emergency preparedness competency training needs and preferred training methods. As a result, competencies for CHC clinicians were identified and priorities for continuing education included CHC individuals' roles and responsibilities, decontamination and containment, and personal preparedness.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In addition to these studies, a substantial volume of literature exists on the preparedness of public health agencies, first responders, and other health professionals. [18][19][20][21][22][23][24][25] However, to date there has been a relative dearth of research on the personal disaster preparedness activities of the general public. What research does exist on the personal preparedness of individuals has either been focused on specific geographic areas, such as Los Angeles, or dealt with terrorism-specific preparedness, and the research has stopped short of using multivariate analysis to identify the factors that most strongly influence personal disaster preparedness.…”
mentioning
confidence: 99%
“…These studies enabled assessment of current emergency preparedness 1 3 protocols, evaluation of the effectiveness of specific procedures within protocols (e.g., use of electronic health record workflows to guide screening), and identification of strengths and areas for improvement. Activities that assess and improve emergency preparedness for infectious diseases in the primary care setting have been relatively underreported, with most published studies either highlighting this as an area of need [11][12][13][14] or showing the willingness of primary care practitioners to help in emergency preparedness and response [11,15].…”
Section: Introductionmentioning
confidence: 99%